Efek Ekstrak Kulit Jeruk Purut (Citrus hystrix DC) terhadap Morfologi dan Histologi Larva Aedes aegypti - Ririh Jatmi wikandari; Surati Surati (Loka Litbang Kesehatan Pangandaran, 2018)
Essential oils can be used as an alternative to naturally control Ae. aegypti. Essential oil can affect morphology and histology of Aedes aegypti larvae. The aims of this study were to determine the effect of larvacide essential oil of kaffir lime against mortality and to know morphological and histological changes of Ae. aegypti larvae. The study was conducted in June 2016 at the Parasitology and Entomology Laboratory of University Jenderal Soedirman. This study was an experimental study with three concentrations and three replications. The death of the larvae is calculated after 24 hours of exposure. Data were analyzed descriptively. The results showed that 103 ppm concentration was effective in killing larvae by 96%. Exposure of kaffir lime peel oils results in the color of the abdomen becoming black. Histological observation preparation larvae showed midgut epithelial cell damage.